Urologic diseases in America project: urolithiasis - Pearle, Margaret S; Calhoun, Elizabeth A; Curhan, Gary C (The Journal of urology, 2005)
We quantified the burden of urolithiasis in the United States by identifying trends in the use of health care resources and estimating the economic impact of the disease. The analytical methods used to generate these results have been described previously. The rate of national inpatient hospitalizations for a diagnosis of urolithiasis decreased by 15% and hospital length of stay decreased from 2.6 to 2.2 days between 1994 and 2000. Rates of hospitalization were 2.5 to 3-fold higher for Medicare beneficiaries with little change between 1992 and 1998. Almost 2 million outpatient visits for a primary diagnosis of urolithiasis were recorded in 2000. Hospital outpatient visits increased by 40% between 1994 and 2000 and physician office visits increased by 43% between 1992 and 2000. In the Medicare population hospital outpatient and office visits increased by 29% and 41%, respectively, between 1992 and 1998. The distribution of surgical procedures remained relatively stable through the 1990s. Shock wave lithotripsy was the most commonly performed procedure, followed closely by ureteroscopy. Overall the total estimated annual expenditure for individuals with claims for a diagnosis of urolithiasis was almost $2.1 billion in 2000, representing a 50% increase since 1994. The cost of urolithiasis is estimated at almost $2 billion annually and it appears to be increasing with time despite a shift in inpatient to outpatient treatment and the emergence of minimally invasive treatment modalities, perhaps because the prevalence of stone disease is increasing.